Flood events and plant level trade: A Chinese experience - Jasmin Katrin Gröschl; Alexander-Nikolai Sandkamp (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2023)
We quantify the impact of large flooding events on the plant-level trade of manufacturing firms in China. Constructing a panel data set of more than 685,000 geolocated plants and provincial city and county measures of flooding events derived from precise geolocated monthly flood areas, we show that the impact on production facilities can be considerable, although relatively short-lived. While the number of exporting plants remains below its pre-flood level for at least 12 months, the effect on the distribution of exporter market scope, on the average exporter scale or the sales distribution of plants vanish within a year. Privately owned plants are hit harder than state-owned enterprises, as they continuously produce fewer products, while their export value recovers. Producing products covered by the Chinese Communist's Party five-year plan tends to insulate firms against the negative effects of floods.
Keywords: F14; F18; Q54; 330; China; trade; firm heterogeneity; natural disasters